The medline UK filter: development and validation of a geographic search filter to retrieve research about the UK from OVID medline. (13th July 2017) - Ayiku, Lynda; Levay, Paul; Hudson, Tom; Craven, Jenny; Barrett, Elizabeth; Finnegan, Amy; Adams, Rachel
Abstract: Background: A validated geographic search filter for the retrieval of research about the United Kingdom (UK) from bibliographic databases had not previously been published. Objectives: To develop and validate a geographic search filter to retrieve research about the UK from OVIDmedline with high recall and precision. Methods: Three gold standard sets of references were generated using the relative recall method. The sets contained references to studies about the UK which had informed National Institute for Health and Care Excellence (NICE) guidance. The first and second sets were used to develop and refine themedline UK filter. The third set was used to validate the filter. Recall, precision and number‐needed‐to‐read (NNR) were calculated using a case study. Results: The validatedmedline UK filter demonstrated 87.6% relative recall against the third gold standard set. In the case study, themedline UK filter demonstrated 100% recall, 11.4% precision and a NNR of nine. Conclusion: A validated geographic search filter to retrieve research about the UK with high recall and precision has been developed. Themedline UK filter can be applied to systematic literature searches in OVIDmedline for topics with a UK focus.